Amorphous titanate-crosslinking N-rich carbon hybrid with 3D channels for fast lithium storage1. Issue 43 (14th May 2015) - Liu, Jiehua; Xu, Jiaqi; Zhou, Kuan; Wang, Lei; Wei, Xiangfeng
<x xml:space="preserve">Abstract</x> A novel amorphous titanate-crosslinking N-rich carbon hybrid is successfully prepared for the first time and exhibits superior high-rate performance.